Russell’s propositional analysis - Amaral, Murilo Garcia de Matos (2020)
The present paper explains what Russell’s method of logical analysis is and how it works in the context of logical atomism, pointing out the objectives and precepts that he considers when he analyzes propositions. After exploring the general development of analysis in his work, I examine two examples of propositional analysis: that of relational propositions and that of propositions which contain descriptions. In both cases, I have noted that Russell seeks to break with a logic which was restricted to the subject-predicate form, once he thought it was the origin of a defective grammar and, thus, also of many of the traditional metaphysical problems. In this sense, assuming that there may be a wide variety of forms, he says that the objective of the analysis would be precisely to identify what is the logical form and what are the constituents of a proposition, which would serve to bring in evidence the misunderstandings of language and so to dissolve metaphysical problems. Therefore, in the present paper, I detail under which theoretical precepts Russell accomplishes this goal in the two specified examples.